2013
DOI: 10.1177/1934578x1300800807
|View full text |Cite
|
Sign up to set email alerts
|

TLC-Image Analysis of Non-Chromophoric Tuberostemonine Alkaloid Derivatives in Stemona Species

Abstract: A simple, selective, precise, and accurate thin-layer chromatographic (TLC) image analytical method was developed and validated for simultaneous quantification of the major components in the root extracts of Stemona. tuberosa (tuberostemonine, tuberostemonine N and neotuberostemonine)), and S. phyllantha (tuberostemonine and tuberostemonine A). The analysis was performed by TLC on silica gel 60 F 254 aluminum plates using a mixture of dichloromethane: ethyl acetate: methanol: ammonium hydroxide (50:45:4:1) as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…() employed HPLC coupled with DAD and ELS detection, while Kongkiatpaiboon et al . () used TLC image analyses for quantification of these alkaloids. In both studies, lower amounts of 1 and 5 were reported.…”
Section: Resultsmentioning
confidence: 99%
“…() employed HPLC coupled with DAD and ELS detection, while Kongkiatpaiboon et al . () used TLC image analyses for quantification of these alkaloids. In both studies, lower amounts of 1 and 5 were reported.…”
Section: Resultsmentioning
confidence: 99%